1996
DOI: 10.1007/s004220050297
|View full text |Cite
|
Sign up to set email alerts
|

A dynamical model for reflex activated head movements in the horizontal plane

Abstract: We present a controls systems model of horizontal-plane head movements during perturbations of the trunk, which for the first time interfaces a model of the human head with neural feedback controllers representing the vestibulocollic (VCR) and the cervicocollic (CCR) reflexes. This model is homeomorphic such that model structure and parameters are drawn directly from anthropomorphic, biomechanical and physiological studies. Using control theory we analyzed the system model in the time and frequency domains, si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
86
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(97 citation statements)
references
References 43 publications
(74 reference statements)
11
86
0
Order By: Relevance
“…After a control trial (natural condition, 43 target steps), the head moment of inertia was increased by eccentrically placed masses attached to a helmet (weighted condition, 43 target steps). This gave an additional moment of inertia of 0.0335 kg ⅐ m 2 to the normal head moment of inertia, which was assumed to be 0.0148 kg ⅐ m 2 , as in Peng et al (1996). This difference corresponds to a 3.3-fold increase.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…After a control trial (natural condition, 43 target steps), the head moment of inertia was increased by eccentrically placed masses attached to a helmet (weighted condition, 43 target steps). This gave an additional moment of inertia of 0.0335 kg ⅐ m 2 to the normal head moment of inertia, which was assumed to be 0.0148 kg ⅐ m 2 , as in Peng et al (1996). This difference corresponds to a 3.3-fold increase.…”
Section: Methodsmentioning
confidence: 99%
“…The plant parameters are selected as (Peng et al, 1996), and h ϭ 100 ms (modified from Tanaka et al, 2006). Instead of 0.1 N ⅐ m ⅐ s/rad in Peng et al (1996), b is selected to be 0.3 N ⅐ m ⅐ s/rad, as in Tangorra et al (2003); this fits the observed head velocity profile better.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, the movement of body allowed both the eye and head deviation to remain within comfortable ranges, while facilitating the redirection of gaze toward a target of interest. It is likely that this eye-head-body gaze reorientation strategy possesses the teleological advantage of ensuring when a second object of interest appears in the vicinity of a current target, a subject can more rapidly align its gaze with the new object since a smaller effort will be required to rotate the eyes (as compared with the head) (Peng et al 1996;Zangemeister et al 1981), or-if required-to rotate the head-onbody as compared with body-in-space.…”
Section: Why Move the Eye Head And Body To Reorient Gaze?mentioning
confidence: 99%
“…Afferent feedback depicted by eFRFs (see Fig. 5B) indicates a magnitude that increases above 1 Hz, which functions to dampen system dynamics at high frequencies (Keshner et al,1995;Peng et al,1996).…”
Section: Head-neck Stabilization and Afferent Feedbackmentioning
confidence: 99%